Using the Saoraja Lapinceng Traditional House as a Media for Local Wisdom Based-Physics Learning on Equilibrium of Rigid Body - Arsyi, Nurul; Arsyad, Muhammad; Palloan, Pariabti; Hasyi, Mutahharah (Jurnal Pendidikan MIPA, 2023)
This study aims to analyze the components of the Saoraja Lapinceng traditional house which can be used as a rigid body equilibrium material. The type of research is descriptive qualitative. Data obtained from interviews, observations, and documentation were analyzed by data reduction, data display, and verification/conclusion drawing. The results showed (1) Supporting poles (Aliri’) which can be used as a center of gravity material, the center of gravity of the house is called posi bola which has the meaning of the center of everything, according to the calculation of the house weight point is located at G = (11.75m); (5,5 m); (2,5 m). (2) Foundations (Pallangga) are used as material for the inertia moment of rigid body with a rectangular shape following the philosophy of Sulapa appa, Inertia moment of pallangga is I= 416,67 (3) Pattolo’ and Arateng can be used as examples of rigid body equilibrium of cantilever beams, the results of the analysis are known that pattolo' and arateng have the following equilibrium equations Στ=2,5FA−0,12mg=0, (4) Stairs (Addengeng) can be used as an example of rigid body equilibrium on a ladder, The stairs have an angle of 40° which is the ideal angle for stairs and have the following equilibrium equations Στ= 3 mg− 0,2 FA =0, (5) Timpa’ Lajja can be used as an example for understanding the concept of a force moment which has a slope angle of 30̊ and signifies a sign of balusu power, namely tellu boccoe, force moment of timpa’ lajja is τ ⃗=0,5 F ⃗.Keywords: physics learning, equilibrium of rigid bodies, local wisdom.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp98-113